Single-crystal X-ray diffraction investigation of the reversible order-disorder phase transition in iron-deficient TlFe2-xSe 2 - Ahrens, E.; Nitsche, F.; Doert, Th.; Ruck, Michael (Crystal Research and Technology, 2014)
A reversible phase transition was found for iron-deficient TlFe 2-xSe2 (x ≈ 0.4) and investigated on single crystals using high temperature synchrotron radiation X-ray diffraction. Full data sets have been collected at room temperature and at 200 °C to evaluate the structures. The high-temperature form (space group I4/mmm, lattice parameters a = 3.8919(3) Å, c = 14.027(3) Å) shows complete statistical disorder of iron positions and vacancies in a ThCr2Si2 type structure. The low-temperature form corresponds to a √5 × √5 superstructure of the ThCr2Si2 type (I4/m, a = 8.6966(2) Å, c = 14.009(9) Å) and shows partial ordering of iron positions and vacancies. A group-subgroup relation can be compiled between both structures. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: iron-deficiency; phase transition; thallium iron selenide; X-ray diffraction